(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In the process of committing a crime, invisible (hidden) traces appear as a result of the criminal’s direct contact with the victim’s body, clothes, and other surrounding objects in some cases. The difficulty of completely destroying or falsifying traces of biological origin increases the importance of these traces as physical evidence. These physical evidences, which are used to identify the suspect, are the most reliable in determining whether the suspect is involved in a crime. The widespread introduction and use of methods that allow for the identification of DNA-preserving biological traces provide an opportunity to quickly solve serious and extremely serious crimes.